Production goes global, compliance stays local: private regulation in the global electronics industry - Distelhorst, G.; Locke, R. M.; Pal, T.; Hiram, S. (Regulation and Governance, 2015)
Poor working conditions in global supply chains have led to private initiatives that seek to regulate labor practices in developing countries. But how effective are these regulatory programs? We investigate the effects of transnational private regulation by studying Hewlett‐Packard's (HP) supplier responsibility program. Using analysis of factory audits, interviews with buyer and supplier management, and field research at production facilities across seven countries, we find that national context – not repeated audits, capability building, or supply chain power – is the key predictor of workplace compliance. Quantitative analysis shows that factories in China are markedly less compliant than those in countries with stronger civil society and regulatory institutions. Comparative field research then illustrates how these local institutions complement transnational private regulation. Although these findings imply limits to private regulation in institutionally poor settings, they also highlight opportunities for productive linkages between transnational actors and local state and society.